Barefoot in the park [videorecording (DVD)] - Saks, Gene, 1921-2015; Redford, Robert; Fonda, Jane, 1937-; Boyer, Charles, 1899-1978; Simon, Neil (Paramount, 2017)
Post-honeymoon blues follows uptight Paul and free-spirited Corie as they adjust to married life in a tiny Greenwich Village apartment.